Laser-assisted hatching of cryopreserved-thawed embryos by thinning one quarter of the zona - Petersen, Claudia Guilhermino [UNESP]; Mauri, Ana Lucia [UNESP]; Razera Baruffi, Ricardo Luiz; Alcântara Oliveira, João Batista; Felipe, Valeria; Massaro, Fabiana Cagnoto; Franco Junior, Jose Gonçalves [UNESP] (Elsevier, 2006)
Laser-assisted hatching is little documented in the literature regarding its efficacy in cryopreserved-thawed (CT) embryo transfer cycles. The aim of the present study was to evaluate in a randomized manner the efficacy of thinning one quarter of the zona pellucida of CT embryos to a depth of 50-80% of the original thickness, via laser treatment (the qLZT-AH procedure), in improving implantation and pregnancy rates. Two populations were studied: population I, patients who had all their supernumerary embryos cryopreserved, regardless of their morphology, and population II, patients at risk of ovarian hyperstimulation syndrome who had all their embryos cryopreserved. Artificial and natural protocols were used for the embryo transfers. A total of 350 laser-thinned CT embryos were compared with 352 intact zona embryos. No difference in implantation or pregnancy rate was found after using qLZT-AH in either population. These findings suggest that qLZT-AH should not be routinely performed in cryopreserved embryo programmes.
Keywords: Cryopreserved-thawed embryos; Implantation; Quarter laser zona thinning; chorionic gonadotropin; estradiol valerate; postoval; progesterone; adult; clinical protocol; clinical trial; controlled clinical trial; controlled study; cryopreservation; diode laser; embryo; embryo transfer; female; hatching; human; major clinical study; nidation; ovary hyperstimulation; patient coding; pregnancy rate; randomized controlled trial; risk assessment; thawing; thickness; zona pellucida; Adult; Cryopreservation; Embryo Implantation; Embryo Transfer; Female; Humans; Lasers; Pregnancy; Sperm Injections, Intracytoplasmic; Zona Pellucida